Prevalence of Pathogenic Germline DICER1 Variants in Young Individuals Thyroidectomised Due to Goitre – A National Danish Cohort - Altaraihi, Mays; Hansen, Thomas van Overeem; Santoni-Rugiu, Eric; Rossing, Maria; Rasmussen, Åse Krogh; Gerdes, Anne-Marie; Wadt, Karin (Frontiers in Endocrinology, 2021)
Introduction: DICER1 syndrome encompasses a variety of benign and malignant manifestations including multinodular goitre, which is the most common manifestation among individuals carrying pathogenic DICER1 variants. This is the first study estimating the prevalence of pathogenic DICER1 variants in young individuals with multinodular goitre. Methods: Danish individuals diagnosed with nodular goitre based on thyroidectomy samples in 2001-2016 with the age limit at time of operation being ≤ 25 years were offered germline DICER1 gene testing. Results: Six of 46 individuals, 13% (CI [3.3;22.7], p <0.05), diagnosed with nodular goitre on the basis of thyroidectomy samples under the age of 25 years had pathogenic germline variants in DICER1. They were found in different pathoanatomical nodular goitre cohorts i.e. nodular goitre (n=2), colloid nodular goitre (n=3) and hyperplastic nodular goitre (n=1). Conclusions: We recommend referral of patients thyroidectomised due to goitre aged <21 years and patients thyroidectomised due to goitre aged <25 years with a family history of goitre to genetic counselling. Patients of all ages thyroidectomised due to goitre, who are affected by another DICER1 manifestation should be referred to genetic counselling.